1982
DOI: 10.1111/j.1365-2273.1982.tb01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of neck node metastasis

Abstract: A retrospective clinico-pathological study has been carried out in a series of 405 patients with squamous cell carcinoma of the head and neck who underwent a total of 484 radical neck dissections. The recurrence rate in the neck in 327 patients who had histological positive nodes was 21.1%. Recurrence in the neck after a standard radical neck dissection almost invariably proved fatal. A statistical analysis has been carried out to evaluate the clinical and pathological factors which are of importance in regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
177
0
23

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(210 citation statements)
references
References 10 publications
10
177
0
23
Order By: Relevance
“…[1][2][3][4] However, the current study is the first study of patients with SCCOT to compare clinical outcomes with respect to clinical and pathologic lymph node stages. Statistically significant differences in survival were found for both cN0 -N2 and pN0 -pN2 stages, although the differences in pathologic staging reached a higher level of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] However, the current study is the first study of patients with SCCOT to compare clinical outcomes with respect to clinical and pathologic lymph node stages. Statistically significant differences in survival were found for both cN0 -N2 and pN0 -pN2 stages, although the differences in pathologic staging reached a higher level of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…This finding has also been recognized in previous large reviews of patients with SCCHN who underwent neck dissection. 4,[47][48][49][50] The presence of ECS is another poor prognosticator. [5][6][7][8][9][10][11][12] ECS may be detected radiographically, 51 but neck dissection remains the only definitive method to identify the presence of ECS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of those who are at greatest risk for developing distant metastasis and mortality from prostate cancer will help stratify patients into prognostically distinct groups. Previous studies demonstrated that assessment of extranodal extension (ENE) in patients who are node positive may provide prognostic information in certain human epithelial malignancies, including breast cancer (10,11), squamous cell carcinoma of the vulva (12,13), gastric carcinoma (14), and squamous carcinoma of the head and neck (15)(16)(17)(18)(19)(20)(21). Others refuted the significance of ENE (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…But study carried out by G.B Snow and his team showed enlarged lymph node <3 cm in 85% and > 3 cm in size in 15% only. 13 …”
Section: Introductionmentioning
confidence: 99%